2021
DOI: 10.1016/j.msard.2020.102641
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of eculizumab in AQP4+ neuromyelitis optica spectrum disorder: Subgroup analyses of the randomized controlled phase 3 PREVENT trial

Abstract: on behalf of the PREVENT Study Group, Benefits of eculizumab in AQP4+ neuromyelitis optica spectrum disorder: subgroup analyses of the randomized controlled phase 3 PREVENT trial, Multiple Sclerosis and Related Disorders (2020), doi:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
14
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 27 publications
2
14
0
2
Order By: Relevance
“…This interim analysis of the OLE provides data on the long-term safety and efficacy of eculizumab from more than twice the number of PY of eculizumab exposure than in PREVENT (median treatment duration of almost 2.5 years). The combined PREVENT and interim OLE eculizumab safety data reported here are consistent with its known safety profile in patients with AQP4-IgG+ NMOSD 11,15 and with its well-characterized safety profile in its other approved indications, paroxysmal nocturnal hemoglobinuria, atypical hemolytic uremic syndrome, and generalized myasthenia gravis, based on clinical trial data and more than 10 years of postmarketing experience. [19][20][21][22][23][24] No new safety signals were observed between the primary analysis of PREVENT and this interim analysis of the OLE.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…This interim analysis of the OLE provides data on the long-term safety and efficacy of eculizumab from more than twice the number of PY of eculizumab exposure than in PREVENT (median treatment duration of almost 2.5 years). The combined PREVENT and interim OLE eculizumab safety data reported here are consistent with its known safety profile in patients with AQP4-IgG+ NMOSD 11,15 and with its well-characterized safety profile in its other approved indications, paroxysmal nocturnal hemoglobinuria, atypical hemolytic uremic syndrome, and generalized myasthenia gravis, based on clinical trial data and more than 10 years of postmarketing experience. [19][20][21][22][23][24] No new safety signals were observed between the primary analysis of PREVENT and this interim analysis of the OLE.…”
Section: Discussionsupporting
confidence: 81%
“…11,12 This benefit of eculizumab was seen across a wide range of patient subgroups based on concomitant immunosuppressive therapy (IST) and past rituximab use, geographical region, age, race, sex, disease duration, relapse history, and disability status. 15 The safety profile of eculizumab in AQP4-IgG+ NMOSD was consistent with that seen for eculizumab in other approved indications. 11,14 We report an interim analysis (data cutoff date was July 31, 2019) of combined data from PREVENT and its ongoing open-label extension (OLE) on the long-term safety and efficacy of eculizumab in patients with AQP4-IgG+ NMOSD.…”
supporting
confidence: 75%
See 2 more Smart Citations
“…We are unaware of factors that might explain these differences between populations. Post hoc analysis has demonstrated that the rates of trial agent-related AEs during PREVENT were similar in patients who received eculizumab with and without concomitant ISTs (217.2 AEs/100 PY and 196.1 AEs/100 PY, respectively) (Palace et al, 2021).…”
Section: Discussionmentioning
confidence: 95%